2017
DOI: 10.1038/ja.2017.11
|View full text |Cite
|
Sign up to set email alerts
|

Ivermectin: enigmatic multifaceted ‘wonder’ drug continues to surprise and exceed expectations

Abstract: Over the past decade, the global scientific community have begun to recognize the unmatched value of an extraordinary drug, ivermectin, that originates from a single microbe unearthed from soil in Japan. Work on ivermectin has seen its discoverer, Satoshi Ōmura, of Tokyo's prestigious Kitasato Institute, receive the 2014 Gairdner Global Health Award and the 2015 Nobel Prize in Physiology or Medicine, which he shared with a collaborating partner in the discovery and development of the drug, William Campbell of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
177
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(179 citation statements)
references
References 114 publications
(92 reference statements)
0
177
0
2
Order By: Relevance
“…However, the therapeutic arsenal for rosacea has improved over the last decades, and currently, there are a number of topical and systemic treatments available such as metronidazole, oxymetazoline, brimunidine, azelaic acid, and tetracyclines (Holmes & Steinhoff, 2017;Steinhoff, Schmelz, & Schauber, 2016). This agent has a similar structure of macrolide antibiotics, and it belongs to a class of broad spectrum anti-parasitic drugs that are isolated from the fermentation of Streptomyces avermitilis (Crump, 2017). This agent has a similar structure of macrolide antibiotics, and it belongs to a class of broad spectrum anti-parasitic drugs that are isolated from the fermentation of Streptomyces avermitilis (Crump, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the therapeutic arsenal for rosacea has improved over the last decades, and currently, there are a number of topical and systemic treatments available such as metronidazole, oxymetazoline, brimunidine, azelaic acid, and tetracyclines (Holmes & Steinhoff, 2017;Steinhoff, Schmelz, & Schauber, 2016). This agent has a similar structure of macrolide antibiotics, and it belongs to a class of broad spectrum anti-parasitic drugs that are isolated from the fermentation of Streptomyces avermitilis (Crump, 2017). This agent has a similar structure of macrolide antibiotics, and it belongs to a class of broad spectrum anti-parasitic drugs that are isolated from the fermentation of Streptomyces avermitilis (Crump, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The most recent available drug for rosacea is the topical ivermectin (IVM) 1% cream: The US Food and Drug Administration approved the use in PPR in December 2014, and 1 year later so was it in Europe (http://www.accessdata.fda.gov/drugsatfda_docs/label/ 2014/206255lbl.pdf; http://www.galderma.com/News/articleType/ ArticleView/articleId/79/Galderma-Announces-Positive-Outcomeof-European-Decentralised-Procedure-for-Approval-of-SOOLANTRAivermectin-Cream-10mgg-for-Rosacea-Patients). This agent has a similar structure of macrolide antibiotics, and it belongs to a class of broad spectrum anti-parasitic drugs that are isolated from the fermentation of Streptomyces avermitilis (Crump, 2017). Real-life experience on effectiveness and tolerability of IVM 1% in a retrospective study based on 50 patients has showed effective response not only in moderate to severe PPR but also in almost clear and mild cases (Trave, Merlo, Cozzani, & Parodi, 2019).…”
mentioning
confidence: 99%
“…S. avermectinius was first isolated from a golf course in Japan26 and has played a pivotal role in the control of lymphatic filariasis and onchocerciasis 14. Its antiparasitic mechanism involves potentiating neurotransmission by disrupting ligand-gated chloride channels in the muscles and nervous system of invertebrates including larvae in the order of Diptera 27.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its favourable safety profile, there has been increasing off-label use and research into repurposing ivermectin for a variety of infectious and non-infectious diseases 26. Successful use of oral ivermectin as an adjunct to manual extraction has been reported in nasal myiasis28–30 and rhino-orbital myiasis 10 20 31.…”
Section: Discussionmentioning
confidence: 99%
“…As worldwide attention on ivermectin and its potential steadily increases, it is becoming increasingly important to recognize that currently available ivermectin contains an imprecise mixture of two compounds [14]. The two component chemicals are extremely similar, compound 1 (ivermectin B1a) having an ethyl group at the C-26 position while compound 2 (ivermectin B1b) has a methyl group.…”
Section: Main Textmentioning
confidence: 99%